Combination of fixative agents and fixation times to visually differentiate the cortical from the medullary layer in bovine adrenal glands - de Oliveira, Fabrício Singaretti [UNESP]; Macitelli, Fernanda; Santos, Caio C. C. [UNESP]; Braga, Janaina S. [UNESP]; Costa, Barbara C. [UNESP]; Pastore, Marina [UNESP]; Rocha, Thiago A. S. S. [UNESP]; Da Costa, Mateus J. R. P. [UNESP] (My University, 2018)
Chronic stress exposure commonly increases adrenals weight and changes their morphology. This study aimed to compare four methods to delimitate the cortical and medullary layers of adrenals glands in Nelore bulls. Fresh adrenals did not present differentiation between layers. Then, frozen adrenals were distributed in plastics bags with fixative Bouin (G1), 96ºGL ethylic alcohol (G2), 10% formaldehyde (G3), or 2.5% glutaraldehyde (G4). After 12 hours of fixation, the G1 adrenal glands did not show the entire cortical layer marked by Bouin’s solution. For G2 and G3 there was a poor contrast, while for G4 there was a reasonable contrast. After 24 hours of fixation, G1 had an excellent contrast between layers, while G2 and G4 had a reasonable contrast and G3 a very bad contrast. After 48 hours it was difficult to differentiate cortical and medullar layers for G1; for Group 2 we get a reasonable contrast; and for G3 the contrast was bad. For G4 the contrast was not as sharp due to the medulla became dark. It was concluded that fixation of adrenals must be done in Bouin’s solution for 24 hours to obtain an effective evaluation of the adrenals’ morphometry.
Keywords: Anatomy; Animal welfare; Gland; Morphometry; Stress